Matthew the Tenth and the Creation of the Third (Lithuanian) Edition of Izmaragd - Юрьевич Темчин, Сергей (Slavistica Vilnensis, 2009)
The author of the article argues that Matthew the Tenth, who copied the 1502–1507 Biblical Miscellany in Vilnius and Suprasl, might also be the author of the new monographic principle of textual organization. The principle was used in the traditional Old Church Slavonic book of Izmaragd during the compilation its its third Lithuanian edition, which was produced in the Suprasl monastery in the first quarter of the sixteenth century. In both cases, essentially the same work was performed: the fragments / texts written by the same author were first extracted from different parts of miscellanies and then put together to produce monographic chapters.